Prepartum heat stress in dairy cows increases postpartum inflammatory responses in blood of lactating dairy cows - Martin Sheldon (Journal of Dairy Science, 2023)
Uterine diseases and heat stress (HS) are major challenges for the dairy cow. Heat stress alters host immune resilience, making cows more susceptible to the development of uterine disease. Although HS increases the incidence of uterine disease, the mechanisms by which this occurs are unclear. We hypothesize that evaporative cooling (CL) to alleviate HS in prepartum cows has carry-over effects on postpartum innate immunity. Nulliparous pregnant Holstein heifers were assigned to receive either forced CL that resulted in cool conditions (shade with water soakers and fans; n = 14) or to remain under HS conditions (barn shade only; n = 16) for 60 d prepartum. Postpartum, all cows were housed in a freestall barn equipped with shade, water soakers, and fans. Respiratory rate and rectal temperature during the prepartum period were greater in HS heifers compared with CL heifers, indicative of HS. Although milk production was decreased in HS cows compared with CL cows, the incidence of uterine disease and content of total or pathogenic bacteria in vaginal mucus on d 7 or d 21 postpartum was not affected by treatment. Whole blood was collected on d 21 and subjected to in vitro stimulation with lipopolysaccharide. Lipopolysaccharide-induced accumulation of IL-1β, IL-10, and MIP-1α was greater in blood collected from HS cows compared with CL cows. Our results imply that prepartum HS during late pregnancy has carry-over effects on postpartum innate immunity, which may contribute to the increased incidence of uterine disease observed in cows exposed to prepartum HS.